2013
DOI: 10.1016/j.str.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants and Mechanism of Mammalian CRM1 Allostery

Abstract: Proteins carrying nuclear export signals cooperatively assemble with the export factor CRM1 and the effector protein RanGTP. In lower eukaryotes, this cooperativity is coupled to CRM1 conformational changes; however, it is unknown if mammalian CRM1 maintains its compact conformation or shows similar structural flexibility. Here, combinations of small-angle X-ray solution scattering and electron microscopy experiments with molecular dynamics simulations reveal pronounced conformational flexibility in mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 44 publications
(65 reference statements)
1
44
0
Order By: Relevance
“…3B). Molecular dynamics simulations suggested that H9 loop interactions are important for maintaining rigidity of the CRM1 ring [91]. …”
Section: A Summary Of Crm1 Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…3B). Molecular dynamics simulations suggested that H9 loop interactions are important for maintaining rigidity of the CRM1 ring [91]. …”
Section: A Summary Of Crm1 Structuresmentioning
confidence: 99%
“…4D to the open groove in Fig. 3D) [91]. Two other structural features are clearly different in the unliganded state.…”
Section: A Summary Of Crm1 Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…These parameters were previously used for simulations of a-solenoid proteins and were shown to give reliable results (31,32,48,49).…”
Section: Simulationsmentioning
confidence: 99%